2006
DOI: 10.1021/jp060139h
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Breakdown in Linear Response of a Rotationally Driven Magnetic Microparticle and Application to Physical and Chemical Microsensing

Abstract: In this work, sensing magnetic microparticles were used to probe both the local pH and the viscosity-dependent nonlinear rotational behavior of the particles. The latter resulted from a critical transition marking a driven particle's crossover from phase-locking to phase-slipping with an externally rotating magnetic field, i.e., a sudden breakdown in its linear response that can be used to measure a variety of physical quantities. The transition from simple rotation to wobbling is described both theoretically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
100
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 31 publications
0
100
0
Order By: Relevance
“…24,[30][31][32] Magnetic rotators with small Helmholtz coils can provide the rotation frequency in the range between 1 Hz to 1 kHz and the ten millitesla field strength. 8,15,21,25,26,28,29,33 The strength and frequency of magnetic field are limited by the coil ability to support high currents. It was shown that small watercooled magnetic coils can maintain sufficiently high rotating magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…24,[30][31][32] Magnetic rotators with small Helmholtz coils can provide the rotation frequency in the range between 1 Hz to 1 kHz and the ten millitesla field strength. 8,15,21,25,26,28,29,33 The strength and frequency of magnetic field are limited by the coil ability to support high currents. It was shown that small watercooled magnetic coils can maintain sufficiently high rotating magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…While many systems have been shown to exhibit nonlinear rotational dynamics, no studies considered single cell detection and growth monitoring applications. Recently, a theoretical treatment on single magnetic particle systems have been developed and demonstrated [8,9], but previous studies did not focus on applications of such systems. To fill this research gap, our group of investigators have studied the nonlinear rotation of magnetic microparticles and explored a number of applications, including single bacterial cell detection [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…where O is the rotational rate of the external field and O c is the critical frequency at which the particle motion changes from being synchronous with the field to being asynchronous [8,9]. This point of criticality is given by…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of an external field, H * ext , the moment of the particle will feel a magnetic torque, t N Á m. For low Reynolds number systems, such as this one where inertial terms are negligible, the rotation frequency of the particle can be determined through the balance between magnetic torque and viscous drag, where g ROT ¼ 8pha 3 , is the torsional friction on a particle of radius a due to a fluid with viscosity h. For sufficiently low rotation frequencies, the particle becomes phase-locked with the external field and follows the equations of motion of a non-linear harmonic oscillator, similar to systems studied by others. [41] For this system, we calculate the critical frequency to be on the order of hundreds of hertz, thus the angular velocity of the particle will nearly always be phase locked with the field. For the sake of comparison, the magnetic torque in our experimental system is three orders of magnitude larger than torques previously reported in similar optomagnetic systems, [17] which is a direct result of the large volume of ferromagnetic material on the surface of these dot Janus particles.…”
mentioning
confidence: 99%